(untitled) (Journal of Management and Social Sciences, 2017)
Abstract The paper examines Maternal Health and recently concluded Millennium Development Goal 5(MGD5) and why there were obstacle(s) to its success in Nigerian society and the need for integrated interventions for the newly developed Sustainable Development Goals. Culture, poverty and lack of political will act as major causes for nonperformance of the (MGD5). The main reasons for this among other things are low utilization of quality of maternal healthcare services, negative opinion of important referents, social, cultural, physical and economic barriers such as patriarchy, long distances, high transport and other indirect costs. The review therefore examined the existing level of maternal and child mortality/morbidity within the extant literatures/statistical abstracts and it was found out that inadequate health care/maternity centres, paucity of physicians and insufficient budgetary allocation wereÂ stumbling blocks to effective maternal health and success of MDG5. It is therefore suggested that government should make available functional primary health care facilities including maternity centres equipped with up to date infrastructures which would be funded equitably to facilitate patronage and easy access to both rural and urban residents. Effort should be made to retain trained professionals in all ramifications Keywords Millennium Development Goal 5(MDG5), maternal health, culture contour, faux pas,Â infrastructure